Determinants of non-performing loans in the banking sector in developing state - Muhammad Asif Khan; Asima Siddique; Zahid Sarwar (Emerald Publishing Limited, 2020)
The size of non-performing loans (NPLs) plays a key role in the stability of the banking sector of a country. The factors that explain the NPLs contain very important information for banks. Studies in this regard with respect to developing states such as Pakistan have received little attention. This study aimed to scrutinize the determinants of NPLs observing a case of the banking sector in Pakistan over the period from 2005 to 2017.The sample consists of the banking sector (i.e., commercial banks) listed in Pakistan Stock Exchange over the period of 2005–2017. The banking factors, including profitability, operating efficiency, capital adequacy and income diversification, were evaluated. The estimations were done by regression modeling using random and fixed effects through STATA software.Results show that the operating efficiency and profitability indicators have a negative association with NPLs but were statistically significant, while capital adequacy and income diversification have a negative association with NPLs but were statistically insignificant.The present study has considered limited banking indicators as determinants of NPLs and was limited to a specific time period from 2005 to 2017.The study is an attempt to investigate various banking factors that affect the NPLs with respect to developing economies such as Pakistan.